Development of the Sikh Community in Jakarta: History and Social Dynamics - Handayani, Lusi (Hanifiya: Jurnal Studi Agama-Agama, 2025)
This study explores the significant contributions of the Sikh community in Indonesia, particularly in Jakarta, which, despite being a minority group, has had a substantial impact on various social, economic, and cultural sectors. Using a descriptive qualitative approach, this research analyzes the social activities carried out by the Sikh community, such as distributing takjil (fast-breaking food) during Ramadan and providing langar (free food) at gurdwaras, as well as the contributions of prominent figures like Gurnam Singh in sports and H.S. Dillon in human rights. The findings show that although Sikhism is not officially recognized by the Indonesian government, the community remains actively involved in fostering interfaith harmony and contributing to social development with inclusivity and tolerance. They uphold values of equality and selfless service, which are reflected in activities that involve people from all walks of life, regardless of religion or ethnic background. Despite challenges related to religious recognition, the Sikh community continues to preserve its traditions and remains committed to making a positive impact in Indonesia. Overall, this research emphasizes that the Sikh community is not only part of Indonesia's diversity but also an agent of change, playing a vital role in building a more inclusive, just, and harmonious society.